Respostas à perda sanguínea aguda em caprinos - Argolo, Erick Paiva de (Universidade Federal Rural do Semi-Árido, 2014)
The present study aimed to evaluate the effects of acute blood loss in goats, due to the removal of 30% of blood volume. Eight mixed-breed, castrated, adult, healthy goats were used, weighing on average 34.75 + 4.3 kg. Clinical, hemogasometrical, hematological, and biochemical parameters were evaluated; as well as systolic, diastolic and mean blood pressure at the following moments: T0, before sampling, T1, T6, T12, T24, and T72, took place one, six, 12, 24, and 72 hours after sampling, respectively; and T8d, T16d, T24d and T32d, took place eight, 16, 24 and 32 days after sampling. From the total volume of blood 30% were taken. The goats presented tachycardia and tachypnea after the blood removal, a temporary rise in temperature occurred one hour after sampling, returning to normal values already in T6h. Packed cell volume decreased from T1h until T12h. The number of red blood cells, however, was different when compared to T0 only after T12h. Total protein and albumin levels were inferior when compared T0 only an hour after a blood loss, and remained as such until T16d and T8d, respectively. The CRT was high in T1h when compared to T0, but no difference was observed when compared to T12h. There was a decrease in serum calcium levels from T1h up until T24h. Glucose rose in T1h until T6h. At T1h, pH, TCO2, bicarbonate values and base deficit were smaller when compared to T0, while the lactate levels markedly increased at this time. The pO2 and SO2 were not altered. The pCO2 presented decreased values only at T24h. Systolic, diastolic and mean blood pressures showed, immediately after sampling, values lower than half of the observed at T0, however there was no difference at T1h. The concentrations of AST, GGT, urea and creatinine remained within the reference range. The acute loss of 30% of blood volume in goats causes noticeable changes in the clinical, hematological, hemogasometrical, and cardiovascular parameters
Responses to acute blood loss in goats
Keywords: Shock; Hypovolemia; Blood; Hemogasometry; Choque; Hipovolemia; Sangue; Hemogasometria; CIENCIAS AGRARIAS::MEDICINA VETERINARIA